Skills associated with line breaks in elite Rugby Union - den Hollander, S.; Brown, J.; Lambert, M.; Treu, P.; Hendricks, S. (Journal of Sports Science & Medicine, 2016)
The ability of the attacking team to break through the defensive line is a key indicator of success as it creates opportunities to score tries. The aim of this study was to analyse line breaks and identify the associated skills and playing characteristics. The 2013 Super Rugby season (125 games) was analysed, in which 362 line breaks were identified and coded using variables that assessed team patterns and non-contact attacking skills in the phases preceding the line break. There was an average of 3 line breaks per game, with 39% of line breaks resulting in a try. Line breaks occurred when the ball-carrier was running fast [61%, x2(4) = 25.784, p = 0.000, Cramer`s v = 0.1922, weak]. At a moderate distance, short lateral passes (19%) and skip passes (15%) attributed to the highest percentage of line breaks [x2(26) = 50.899, p = 0.036, Cramer`s v = 0.2484, moderate]. Faster defensive line speeds resulted in more line breaks [x2(12) = 61.703, p < 0.001, Cramer`s v = 0.3026, moderate]. Line breaks are associated with overall team success and try scoring opportunities. Awareness of the defenders line speed and depth, fast running speed when receiving the ball and quick passing between attackers to the outside backs creates line break opportunities. During training, coaches should emphasise the movement speed of the ball between attackers and manipulate the speed and distance of the defenders.